Rationing Change as Coping Strategy Employed by Buhid Households against Food Insecurity - Declaro-Ruedas, Mary Yole Apple (JPAIR Multidisciplinary Research, 2015)
The Mangyans as a group of people traces a history of marginalization both in their ancestral domain and in their access to basic social services, particularly, health and education. This study was conducted to: 1) determine the socio-economic characteristics and household food expenditures of the Buhid women; 2) determine their food security condition; and 3) identify the food insecurity coping strategies employed. The descriptive method was employed. The United States Department of Agriculture (USDA) Food Sufficiency Questionnaire and Coping Strategy Index (CSI) was used to enumerate both frequency and severity of coping strategies of households faced with short-term insufficiency of food. Results show that majority of the Buhid women were between 20 and 39 years old, which means that they were still in their middle age and can still perform reproductive and productive activities. They have big household size, with low level of basic education, and with an average monthly income below the poverty threshold. The biggest portion of the household expenditure was spent for food. The Buhid women experienced "food insecurity with moderate hunger" in which adults in the households have experienced reductions in food intake. It is recommended that further study on the relationship between the socio- economic characteristics of the Buhid women and household security status and their coping strategies be conducted.